Pengaruh Kualitas Pelayanan Terhadap Kepuasan Konsumen Pada SPBU Klaligi Kota Sorong - Markskal France Selly; Marthen Nauw; Ratnasari Rana Bulan (Politeknik Kampar, 2023)
This study aims to determine the Influence of Service Quality on Customer Satisfaction at Coco Ulakkarang Gas Station in Padang. The data collection methods used in this study were field research and literature research. The data analysis method used in this study is simple linear regression. The results of the study show that the t-test results indicate that the service quality variable has a significant effect on customer satisfaction, as evidenced by a calculated t-value of 3.530, which is greater than the critical value, and a calculated significance value of 0.000, indicating that the service quality variable has a significant effect on customer satisfaction.